Cyber security: what are we talking about?. Issue 7 (July 2021) - Furnell, Steven; Collins, Emily
Abstract : The term 'cyber security' is increasingly commonplace in everyday life, and is something that users of all ages will encounter in some form. However, there are varying interpretations about what it actually means, and because of this, people have similarly varying assumptions about the extent to which it applies to them or might affect them.